2013
DOI: 10.3389/fpsyg.2013.00148
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Transfer of Perceptual Learning in Accented Speech

Abstract: The perception of speech sounds can be re-tuned through a mechanism of lexically driven perceptual learning after exposure to instances of atypical speech production. This study asked whether this re-tuning is sensitive to the position of the atypical sound within the word. We investigated perceptual learning using English voiced stop consonants, which are commonly devoiced in word-final position by Dutch learners of English. After exposure to a Dutch learner’s productions of devoiced stops in word-final posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…Since Norris et al's (2003) influential work, several studies have shown that perceptual category boundary locations for segmental contrasts are affected by ambiguous sounds when the ambiguous sounds are recognized by the listener as a part of a legitimate word (Clarke & Luce, 2005;Eisner et al, 2013;Kraljic & Samuel, 2005;Maye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Norris et al's (2003) influential work, several studies have shown that perceptual category boundary locations for segmental contrasts are affected by ambiguous sounds when the ambiguous sounds are recognized by the listener as a part of a legitimate word (Clarke & Luce, 2005;Eisner et al, 2013;Kraljic & Samuel, 2005;Maye et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…If so, then position and/or context-sensitive representations of phonemes (Dahan & Mead, 2010;Eisner et al, 2013;Mitterer et al, 2013) would predict more distinct phonetic representations of contrasts in positions and contexts where segments are less predictable, and word-specific phonetic representations (Bybee, 2000;Johnson, 2004;Klatt, 1979;Pierrehumbert, 2002;Wedel, 2006) would predict more distinct phonetic representations of less predictable words.…”
Section: Discussionmentioning
confidence: 99%
“…67-78). 1 Despite the frequent use of SSBE in recent research on speech perception (e.g., Faulkner et al, 2012;Eisner et al, 2013) and the existence of non-acoustic impressionistic descriptions of this variety (e.g., McMahon, 2002), there are no comprehensive acoustic descriptions of the vowels in its vowel system. Perhaps the most complete acoustic descriptions are Deterding (1997) and De Jong et al (2007), but none of these includes all 11 monophthongs or any of the five diphthongs that are recognized in McMahon's (2002) non-acoustic description.…”
Section: Introductionmentioning
confidence: 99%
“…As listeners encounter foreign-accented speech, established lexical knowledge can inform them of a poor mapping from the acoustic signal to native phonetic categories and elicit adjustments in the sound-to-category mappings (Eisner, Melinger & Weber, 2013;Reinisch & Holt, 2014;Sumner, 2011). For instance, a French-accented /p/ sound is acoustically more similar to a /b/ than a /p/ when mapped onto distributions of native English.…”
Section: Perceptual Adaptation To Non-native Accentsmentioning
confidence: 99%
“…Of note, even amidst multiple nonstandard cues in accented speech, listeners can still accurately track the specific variation tagged to a nonstandard phoneme, suggesting that listeners adjust to the specific qualities that make the phoneme nonstandard (e. g., Reinisch & Holt, 2014;Eisner et al, 2013). Variability in production, per se, does not seem to be an obstacle to adaptation.…”
Section: Perceptual Adaptation To Non-native Accentsmentioning
confidence: 99%